Report of prefeasibility study of an expanded leather and shoe industry in West Africa to 1980 (Niamey : Economic Commission for Africa, 1966)
This report covers the leather-and shoe-industry prospects in West Africa.
Economic Commission for Africa Sub-regional Meeting on Economic Co-operation in West Africa Niamey, 10-22 October 1966.
rpm 15/02/2019
Ref
Keywords: Industrialization; Leather and Shoe Industry; West Africa